Desain Pintu Air Berbantu Komputer Untuk Saluran Irigasi Tersier : Computer Aided Design for Sluiced Gate in Tertiary Irrigation Canal - Kukuh Aldi; Budi Indra Setiawan (Departemen Teknik Sipil dan Lingkungan, IPB University, 2020)
The effort of human creativity in the field of hydraulics in overcoming the problem of irrigation, one of which is using floodgates. The discharge from the floodgates needs to be adjusted to the water needs of the plant. However, due to the long design process, the computer aided design of sluice on tertiary irrigation channels is needed in order to be able to set the optimum dimensions and output discharges of crops water needs with fast design time. The tool used in the form of a computer device with Ms Excel and AutoCAD software and materials used were secondary data, that is water needs of local varieties of rice plants in Mangkung, Rambitan, NTB on an area of 50 ha. The data’s then calculated and the largest discharge is 0.12 m3/s with plant evapotranspiration of 5.10 mm/day and 6.43 mm/day of effective rainfall, meanwhile the smallest is 0.02 m3/s with plant evapotranspiration of 3.17 mm/day and 3.47 mm/day of effective rainfall. The dimensions of the steel sluice gates obtained are width of sluice gate 0.40 m, height of sluice gate is 0.80 m with an estimated cost of making Rp 7,547,000 per one sluice. The dimensions of the GFRP sliding sluice gates are width of sluice gate 0.50 m, height of sluice gate is 0.75 m with an estimated construction cost of Rp 7,547,000 per one sluice.